Ответы 2

  • Ответ:

    3/(x+3) + (x+4)/(x^2-9)=(3(3x-3)+x+4)/((x2-9))=(3x-9+x+4)/(x2-9)=(4x-5)/(x2-9)

  •  \frac{3}{x + 3}  +  \frac{x + 4}{ {x}^{2} - 9 }  =  \frac{3}{x + 3}  +  \frac{x + 4}{(x - 3)(x + 3)}  =  \frac{3(x - 3) + x + 4}{(x - 3)(x + 3}  =  \frac{3x - 9 + x + 4}{(x - 3)(x + 3)}  =  \frac{4x - 5}{(x - 3)(x + 3)}  =  \frac{4x - 5}{ {x}^{2} - 9 }

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years